English as Foreign Language (EFL) Teacher’s Questioning Strategies in Classroom Interaction - Nashruddin Nashruddin; Putri Rahmawati Ningtyas (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
ABSTRACT The objectives of this research were to find out the teacher’s questioning strategies, types of the questions, and the reasons of using the questioning strategies in classroom interaction.. This qualitative research using discourse analysis approach. The sample of this study was a teacher of SMPN 1 Tanete Riaja, Barru Regency Data collection of this research was conducted through recording, observation, and interview. The data collected were analyzed through conversational analysis that was used in analyzing teacher's questioning strategies, types of the teacher's questions, and the reasons for using questioning strategies in EFL classroom. The research findings showed that the teacher used questioning strategies by applying some types of questions. The open/ closed questions and knowledge questions were used dominantly by the teacher. It depends on the material that the teacher transferred to the students. Otherwise, synthesis and evaluation questions were used only a few times by teacher. The teacher also applied some strategies, namely questioning in the opening session, questioning in the middle of teaching, prompting the questions, probing the question, and gave reinforcement to the students. The research finding indicated the positive effects of questioning strategies which were applied by the teachers toward EFL Classroom. It was proved by the students’ participation in learning. Moreover, it was shown by the observation sheets that the teacher and all students did a good interaction teaching-learning process.